A COMPROMISE ALLOCATION IN MULTIVARIATE STRATIFIED SAMPLING IN PRESENCE OF NON-RESPONSE - Raghav, Y. S.; Ali, I.; Bari, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we have considered the problem of determining the optimum allocation of sample sizes and sampling fractions for all the characteristics, which minimizes the coefficients of variance among the non respondent to various characteristics under study. The problem is formulated as a Multi objective Programming Problem (MNLPP) and Multi objective Goal Programming Problem. A solution procedure is developed by using Lagrange Multiplier’s Technique (LMT) and Goal Programming technique. A numerical illustration is presented to the computational details.